THE EFFECT OF ANNEALING TEMPERATURES ON PHASE AND OPTICAL PROPERTIES OF TIO2 NANOPARTICLES FOR SOLAR CELL APPLICATIONS - A. Zareen; S. Ali; M. Irfan (European Scientific Journal, ESJ, 2014)
In this research work, effect of annealing temperatures on different properties of TiO2 nanoparticles is being reported for Solar Cell applications. The nanoparticles were synthesized using Sol Gel Method. The solution of ethanol and distilled water was poured drop-wise into the solution of Titanium Butoxide (Ti (OC4H9)4) and Hydrochloric Acid (HCl). The precursor of nanoparticles was annealed at 200oC, 450oC and 650oC. The structure and phase determination was obtained using XRD analysis which confirmed very small crystallite size in the range of 6nm to 18nm and amorphous to anatase to rutile transformation with increased in annealing temperatures. UV-Vis spectroscopy helped in studying the influence of temperature on absorption, transmission and reflection with a remarkable red shift. The study revealed that the band gap decreases with increasing temperature.